Structure Dependence of Fe‐Co Hydroxides on Fe/Co Ratio and Their Application for Supercapacitors. (25th October 2016) - Jiang, Liyang; Sui, Yanwei; Qi, Jiqiu; Chang, Yuan.; He, Yezeng; Meng, Qingkun; Wei, Fuxiang; Sun, Zhi; Jin, Yunxue
Abstract : Fe‐Co hydroxides with different Fe/Co atomic ratios grown on nickel foams are synthesized by one‐step electrochemical deposition. The prepared samples are characterized by X‐ray diffraction, X‐ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy. It was found that the influence of initial Fe/Co ratios in the precursor solutions on the structure and electrochemical performance of electrodeposited products is significant. Fe(OH)3 shows particle shape with average diameter of 200 nm. With addition of Co ions, frame‐like structure consisting of smaller particles is formed for Fe‐Co hydroxides. Based on the morphology of Co(OH)2, it is deduced that Co(OH)2 serves as a network former constructing a tridimensional frame network structure. Fe‐Co hydroxide with Fe/Co ratio of 1:1 exhibits two types of structure features: nanoflake‐like network structure overall and nanoparticle structure with numerous mesoporous microscopically. As the supercapacitor electrode materials, the as‐prepared Fe‐Co hydroxide electrode with Fe/Co ratio of 1:1 exhibits highest specific capacitance of 2255.6 F g −1 at the current density of 1 A g −1 and also shows good cycling performance of 73.5% capacity retention at current density of 10 A g −1 after 2000 cycles. This work provides a facile method to produce promising Fe‐Co hydroxide electrode materials with high performance for supercapacitors. Abstract : Fe‐Co hydroxides with different Fe/Co atomic ratios are synthesized by one‐step electrochemical deposition . Two types of structure features are obtained in Fe‐Co hydroxides: nanoflake‐like network structures overall and nanoparticle structures with numerous microscopic mesopores. As the supercapacitor electrode materials, Fe‐Co hydroxide electrode with Fe/Co ratio of 1:1 exhibits excellent electrochemical capacitance performance.